2013
DOI: 10.1128/aem.01914-13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Viral Photosynthetic and Capsid Protein Genes from Cyanophages in Two Large and Deep Perialpine Lakes

Abstract: Cyanophages are important components of aquatic ecosystems, but their genetic diversity has been little investigated in freshwaters. A yearlong survey was conducted in surface waters of the two largest natural perialpine lakes in France (Lake Annecy and Lake Bourget) to investigate part of this cyanophage diversity through the analysis of both structural (e.g., g20) and functional (e.g., psbA) genes. We found that these cyanophage signature genes were prevalent throughout the year but that the community compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Currently, a range of host-derived metabolic genes have been used as signature biomarkers to investigate the genetic diversity and the evolutionary relationship of cyanophages from cultured and environmental samples (Table 1). The cyanophage-encoded photosynthesis genes psbA and psbD have been used as additional marker molecules to investigate the genetic diversity and evolution of phage populations in natural aquatic environments [100,101,102,103,104]. Phylogenetic analyses, based on the psbA gene, indicated that cyanophages from freshwater environments possess an evolutionary history different from their marine counterparts.…”
Section: Signature Markers For Cyanophage Evolutionmentioning
confidence: 99%
“…Currently, a range of host-derived metabolic genes have been used as signature biomarkers to investigate the genetic diversity and the evolutionary relationship of cyanophages from cultured and environmental samples (Table 1). The cyanophage-encoded photosynthesis genes psbA and psbD have been used as additional marker molecules to investigate the genetic diversity and evolution of phage populations in natural aquatic environments [100,101,102,103,104]. Phylogenetic analyses, based on the psbA gene, indicated that cyanophages from freshwater environments possess an evolutionary history different from their marine counterparts.…”
Section: Signature Markers For Cyanophage Evolutionmentioning
confidence: 99%
“…It is now recognized that the ssDNA viral community has been largely underestimated (because of technical constraints, such as insufficient staining in fluorescence-based methods such as flow cytometry and epifluorescence microscopy, or insufficient material when using PFGE). Its importance (both in terms of diversity and/or abundance) has been highlighted in lakes [23,38], desert ponds of the Mauritanian Sahara desert [10], reclaimed water [37], aquifers [45], stromatolithes [9], corals [55], ground and marine sediments [18,20,60], coastal estuaries [21,22,27] and the ocean in general [1,4,53].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the g20 gene fragment was used as a genetic marker [14,15]. The marker is widely used in the analysis of cyanophages associated with a variety of water ecosystems [14][15][16][17][18][19][20].…”
mentioning
confidence: 99%